Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s00381-020-04728-x
|View full text |Cite
|
Sign up to set email alerts
|

Managing NF2-associated vestibular schwannomas in children and young adults: review of an institutional series regarding effects of surgery and bevacizumab on growth rates, tumor volume, and hearing quality

Abstract: We reviewed our experience in managing of NF2-associated vestibular schwannoma (VS) in children and young adults regarding the effect of surgery and postoperative bevacizumab treatment. A total of 579 volumetric and hearing data sets were analyzed. The effect of surgery on tumor volume and growth rate was investigated in 46 tumors and on hearing function in 39 tumors. Long-term hearing follow-up behavior was compared with 20 non-operated ears in additional 15 patients. Sixteen operated VS were treated with bev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Prior studies have shown that vascular permeability can be related to schwannoma growth, 23 and NF2-related schwannomas can grow faster than sporadic schwannomas. 24 Further studies with a larger sample size would be necessary to confirm our results. Second, a combination of 1.5-T and 3-T scanners were used, which may add heterogeneity to the calculated ADC and DSC-MRI parameters.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Prior studies have shown that vascular permeability can be related to schwannoma growth, 23 and NF2-related schwannomas can grow faster than sporadic schwannomas. 24 Further studies with a larger sample size would be necessary to confirm our results. Second, a combination of 1.5-T and 3-T scanners were used, which may add heterogeneity to the calculated ADC and DSC-MRI parameters.…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, NF2‐related schwannomas showed higher CBV and CBF than sporadic schwannomas with diagnostic performance of .91 and .95 AUCs in this study. Prior studies have shown that vascular permeability can be related to schwannoma growth, 23 and NF2‐related schwannomas can grow faster than sporadic schwannomas 24 . DSC‐MRI technique can be more helpful to differentiate sporadic from NF2‐related schwannomas than DCE‐MRI technique, which revealed diagnostic performance of .90 AUC by permeability parameters of Ktrans and Ve in prior studies 18 .…”
Section: Discussionmentioning
confidence: 88%
“…This approach is justified because remnant tumors after subtotal resection demonstrate a much slower postoperative growth rate of 0.68 mm 3 per year. 12,13 The patient's perception of facial paralysis within the broader setting of NF2, in our experience, cannot be overemphasized. In distinction to most other facial paralysis patients, the timing of surgery for facial paralysis seems less "urgent" for NF2 patients.…”
Section: Preoperative Considerationsmentioning
confidence: 77%
“…In addition, some centers use radiation therapy and bevacizumab in selected patients. 54 In the modern era, few patients with NF2 who have access to specialized neuro-otologic treatment die due to vestibular schwannomas. Operative mortality is less than 1% and recurrence rates are minimal.…”
Section: Resultsmentioning
confidence: 99%